Toward a Poetics of the Interview in Thomas Meinecke. Issue 1 (2nd January 2016) - Bowles, Daniel
Abstract : To explore and elucidate the poetics of the literary interview, one must turn to the master of the genre: contemporary German author Thomas Meinecke. By reassessing Meinecke's many interviews, both those he has sampled in his novels and those he has given to the media, this article aims to illuminate the author's poetic process and to underscore a recent historical shift in the poetic function of the interview. By reading Meinecke's interviews through the lens of his intertextual practices, we ultimately uncover a dialectics of dialogue at the heart of his poetic program. That Meinecke's writing is predicated on a poetics of the interview allows us both to reevaluate received presumptions of authorship and authenticity surrounding the interview and to better understand the narratological function of the interview in Meinecke's published oeuvre.